Digital Transformation in Formative Assessment of Accounting: A Correlational Analysis of Students Perceptions of Gamification, Learning Analytics, and Perceived Usefulness - Dian Normalitasari Purnama; Niken Purnamasari; Nurul Hidayah; Aflaha Aziza Awalina (Assets: Jurnal Akuntansi dan Pendidikan, 2026)
The rapid advancement of digital technology has transformed formative assessment practices in accounting education by enabling real-time, adaptive, and data-driven feedback. However, the implementation of digital formative assessment remains limited, often lacking personalization and engagement. This study aims to analyze students perceptions of gamification, learning analytics, and perceived usefulness in the context of digital formative assessment in accounting. Using a quantitative correlational design with an ex post facto approach, data were collected from accounting education students at Universitas Negeri Yogyakarta through a Likert-scale questionnaire. Validity and reliability tests confirmed that 30 out of 40 items were valid and reliable. Multiple regression and PLS-SEM analyses revealed that both gamification and learning analytics significantly influence perceived usefulness, with learning analytics being the dominant predictor (? = 0.651, p < 0.001), while gamification showed a smaller yet significant effect (? = 0.166, p = 0.017). The model explained 61% of the variance in perceived usefulness (R² = 0.610) and met the goodness-of-fit criteria (SRMR = 0.076). These findings underscore that students acceptance of digital formative assessment is more strongly determined by the analytical value and actionable insights provided by learning analytics than by the motivational effects of gamification. The study contributes to extending the Technology Acceptance Model (TAM) within digital accounting education, suggesting that integrating learning analytics with gamification enhances both engagement and perceived usefulness in formative assessment design.